The Influence of Store Atmosphere, Customer Value and Halal Labeled Products on Customer Loyalty with Customer Satisfaction as a Mediating Variable at Miss Glam Padang City - melisa, melisa; Syafrizal, Syafrizal; Hendri Yeni, Yulia (DINASTI RESEARCH, 2024)
This study aims to determine the effect of store atmosphere, customer value and halal labeled products on customer loyalty with customer satisfaction as a mediating variable at Miss Glam Padang City. The method used in this research is quantitative. The number of samples used was 150 samples. Sampling is done with purposive sampling technique. Sample collection was carried out using a questionnaire via google form and questionnaire. The data analysis method used to prove the correctness of the hypothesis is carried out using Structural Equation Modeling (SEM) through Smart PLS version 4 software. From the results of hypothesis testing, it is found that store atmosphere has no significant effect on customer loyalty, customer value has a significant effect on customer loyalty, halal labeled products have no significant effect on customer loyalty, store atmosphere has no significant effect on customer satisfaction, customer value has a significant effect on customer satisfaction, halal labeled products have a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, store atmosphere has no significant effect on customer loyalty mediated by customer satisfaction, customer value has a significant effect on customer loyalty mediated by customer satisfaction, and halal labeled products have a significant effect on customer loyalty mediated by customer satisfaction.